Predictors of Drug-Resistant Epilepsy in Tuberous Sclerosis Complex. (December 2017) - Jeong, Anna; Nakagawa, Jo Anne; Wong, Michael
Utilizing the multicenter TSC (tuberous sclerosis complex) Natural History Database including 2034 subjects, this study aimed to identify predictors of drug-resistant epilepsy in TSC. Basic epilepsy data were available for 1965 individuals in the database. Supplemental data were further collected from 1546 of these subjects through directed site queries, addressing additional epilepsy characteristics including the presence of drug-resistant epilepsy, therapies trialed, and outcomes of specific therapies. Epilepsy was reported in 86.4% of individuals with TSC. Infantile spasms were reported in 45.2% of individuals and focal seizures were reported in 84.4% of individuals. In those with focal epilepsy, drug resistance was reported in 59.6%, with focal seizure onset prior to age 1 year (odds ratio [OR] 1.9, confidence interval [CI] 1.4-2.5, P < .001), infantile spasms (OR 2.0, CI 1.5-2.5, P < 0.001), and infantile spasms incompletely responsive to therapy (OR 47.6, CI 6.7-333.3, P < 0.001) being associated with an increased likelihood of drug resistance.